Optimization of electrochemical hydrogen compression through computational modeling. (12th September 2022) - Aziz, Majid; Aryal, Utsav Raj; Prasad, Ajay K.
Abstract: One of the main challenges in developing the hydrogen infrastructure is the distribution and storage of hydrogen. A common method to store hydrogen is as a compressed gas. Electrochemical compression (ECC) is a promising technology that can overcome some of the disadvantages of conventional mechanical compressors. ECC employs an externally powered electrochemical cell containing a polymer electrolyte membrane to compress the gas. This work presents a comprehensive 3D ECC model developed for a single cell using COMSOL Multiphysics 5.6 that incorporates all relevant physical and electrochemical processes, and examines the effect of key parameters on ECC performance. It also considers the important phenomenon of back diffusion resulting from the high-pressure differential between the cathode and anode during compression. Results from the current simulations were validated against experimental results obtained previously in our lab. Simulations were first conducted for the unpressurized cathode to understand the effect of membrane thickness, relative humidity of the anode hydrogen supply, temperature, and gas diffusion layer thickness on ECC performance. Next, simulations were conducted for the pressurized cathode, with and without considering back diffusion. In the absence of back diffusion, the pressure ratio reaches the value predicted by the Nernst equation. However, the presence of back diffusion greatly reduces the pressure ratio as was also observed in experiments. The study reveals that three parameters in particular viz. Membrane thickness, operating temperature, and voltage must be carefully selected to optimize ECC operation. These results also suggest that ECC is a viable alternative to conventional technologies for hydrogen compression. This work also provides a foundation for the modeling and analysis of full-scale ECC systems. Highlights: 3D isothermal model for a parallel-flow ECC is implemented in COMSOL Multiphysics. Model accounts for the important phenomenon of back diffusion. Unpressurized and pressurized cathode cases are investigated. Simulation results are validated against our experimental results. Tradeoffs between various objectives are examined for optimal ECC operation.